NGO Initiatives and its Impacts on the Reintegration of Bangladeshi Female Returnee Migrant Workers (The Chittagong University Journal of Social Sciences, 2025)
In recent times, female migration for work has become an important phenomenon in the migration sector in Bangladesh. Unfortunately, a considerable number of female migrant workers are returning home from the Middle East due to various challenges and hardships facing abroad. This unexpected return is causing their reintegration process more stressful. Different migration-focused NGOs are working to reintegrate returned female workers in Bangladesh. The present study aims to explore the major initiatives of migration-focused NGOs of Bangladesh and address the answers of the questions of what are the NGOs’ initiatives to reintegrate returnee women and what are the impacts of these initiatives upon returnees’ reintegration. This study applies qualitative techniques of data collection and analysis based on 16 interviews among different categories of participants. The findings of the study suggest that NGOs’ initiatives and strategies are very effective and helpful to bring changes and alleviate misery of returnee women. However, this study also argues that a major portion of returnee women are out of NGO activities due to lack of comprehensive and coordinated plan of actions which make the successful reintegration of returned migrant women more complex.
Keywords: Female migration; returnee migrants; reintegration; NGOs strategies; Bangladesh